Pengaruh Pengaruh Kualitas Produk Tabungan Haji Zam-Zam Terhadap Minat Nasabah Di Panin Dubai Syariah Bank KC HR. Muhammad Surabaya - Ahmad Balya, Toifur; Sandi, Misella (LP2M IBK Nitro, 2026)
The rapid growth of Islamic banking in Indonesia has led to various financial product innovations, including hajj savings. Panin Dubai Syariah Bank KC HR. Muhammad Surabaya offers the Zam-Zam Hajj Savings as a solution for the community in preparing for the pilgrimage. This study aims to evaluate the product quality of Zam-Zam Hajj Savings, customer interest level, and the extent to which product quality influences saving interest. The research employed a quantitative approach by distributing questionnaires to 30 respondents, then analyzed using validity, reliability, classical assumption tests, and simple linear regression. The results indicate that most respondents (63%–80%) rated the product quality as very good, while saving interest was also high (53%–70%). Regression analysis revealed a positive and significant influence of product quality on customer interest, with a contribution of 70.6%, while the remaining percentage is influenced by other external factors. Thus, the Zam-Zam Hajj Savings product proves to be effective in attracting public interest to save at Panin Dubai Syariah Bank.